2015
DOI: 10.1080/14786419.2015.1062004
|View full text |Cite
|
Sign up to set email alerts
|

A new lanostane-type triterpene and sesquiterpene lactones fromVernonia leopoldiiand theirin vitrocytotoxicity

Abstract: Investigation of the aerial parts of Vernonia leopoldii (Sch. Bip.) Vatke afforded a new lanostane-type triterpene along with known hirsutinolide-type sesquiterpene lactones and flavonoid glycosides, all are identified for the first time in this species. The new compound was identified as lanost-3β, 23S-dihydroxy-22(31)-ene. The structures of the isolated compounds were elucidated based on spectroscopic evidence. The hirsutinolides and the triterpene were evaluated for their cytotoxicity against four human can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In addition, it is widely used for the treatment of cancer ( Tuasha et al, 2022 ). Recently, a new triterpene isolated from the aerial part of this plant has shown an appreciable cytotoxicity against several cancerous cell lines ( Marzouk and Abd Elhalim, 2016 ). Laggera tomentosa (A.Rich.)…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is widely used for the treatment of cancer ( Tuasha et al, 2022 ). Recently, a new triterpene isolated from the aerial part of this plant has shown an appreciable cytotoxicity against several cancerous cell lines ( Marzouk and Abd Elhalim, 2016 ). Laggera tomentosa (A.Rich.)…”
Section: Resultsmentioning
confidence: 99%
“…Marzouk and Abd Elhalim [72], using NMR technique, found in the extract of V. leopoldii aerial parts compounds previously not reported in the literature, characterized as sesquiterpene lactones, triterpene tetracyclic and apigenin-7-O-glucide and luteolin-7-O-glucide. According to the authors, chemical and pharmacological investigations have shown that the sesquiterpene lactones found in plants of the genus Vernonia present antitumor activities, and some sesquiterpene lactones may exhibit strong cytotoxicity against tumor cell lines.…”
Section: Explorative Analyses: Correlations Between Phytochemicals Antioxidant Activity and Anticancer Effectsmentioning
confidence: 94%
“…Among species of Vernonia, antitumor properties have been described Vernonia amygdalina [5,11,47,48,49], Vernonia bockiana [50], Vernonia cinerea [51,52,53], Vernonia condensate [54], Vernonia divaricata [43], Vernonia extensa [44], Vernonia fimbrillifera [55], Vernonia glaberrima [56,57], Vernonia kotschyana [58], Vernonia leopoldii [59], Vernonia mespilifolia [60], Vernonia pachyclada [61], Vernonia paniculata [62], Vernonia patula [63], Vernonia polyanthes [64], and Vernonia scorpioides [65,66,67], Vernonia zeylanica [42,68].…”
Section: Genus Antitumor Activitymentioning
confidence: 99%